Tolerance of triads, police legitimacy, and self-help amidst the Umbrella Movement - Lo, Tit Wing (The Australian and New Zealand journal of criminology, 2019)
The 79-day Umbrella Movement in 2014 is the largest civil disobedience movement in Hong Kong’s history. Based on a sample of 186 protesters and 503 students, the present paper aims to examine the protesters’ tolerance of triad activities; their perceptions of the police, of triad protection of occupiers, and of triad weiwen (maintenance of stability for the government); and the relationship between police legitimacy and tolerance of triad activities. We found that attitudes toward democracy, toward the importance of national identities, and toward triad involvement, and negative perceptions of the police were all significant predictors of an individual’s support for the Movement. We further found that the predictors we had identified earlier were able to significantly differentiate protesters from student opponents. When compared with students, protesters had lower ratings for police procedural justice and were more tolerant of triad legal behavior and of protecting protesters, but less tolerant of triad illegal behaviors and weiwen. Implications of Hong Kong’s self-help movement are discussed.